Tort Liability for Environmental Pollution - MANASRA, Majd Waleed; Al MAMARI, Said; GHARIBEH, Ashraf; NAJM, Muhammad; YOUNES, Anan Shawqi; ALSHARQAWI, Ahmad Hussein (Journal of Environmental Management and Tourism, 2022)
This research is concerned with stating the legal provisions set for tort liability of environmental Pollution as stated by the Environmental Protection Law No. 6 of 2017 and its amendments. In fact, and at the beginning, the research approached the definitions of each of the terms of environmental Pollution, types, and sources of ecological Pollution according to the methodology of the Jordanian legislators. Further, the Environmental Protection Law No. 6 of 2017 and its amendments and Jordanian Civil Law No. (43) Of 1976 were analyses, after which the elements on which the tort liability is based were concluded, followed by examining some of the cases presented to the Jordanian judiciary.